Pengayaan Literasi Keagamaan Melalui Akses Buku Keagamaan Penyuluh Agama Di Sulawesi Utara - Eko Putro, Zaenal Abidin (Jurnal Lektur Keagamaan, 2020)
The role role of religious instructors (penyuluh agama) supervised by the Ministry of Religious Affairs (MoRA) are very important in Indonesian society. It is assumed that they can contribute to maintain harmonious life in society and to foster moderation in terms of religious understanding among Indonesian people. Previously, they had only served society with special forces such as policeman, military, student living in dormitory, etc. But now they provide religious assistant to broader society. However, attentions to this group is still a bit low especially regarding with access to religious textbooks and literatures. This paper, which is the result of field research that was conducted in Manado and its surrounding area and using mixed method, has shown how the religious instructors gain their access to religious literatures. One of important research findings was that the religious instructors could be able to suffice their religious textbooks as well as religious literature by themselves autonomously.Keywords: literacy, expressive revolution, religious instructors, religious litetarures. Peran para penyuluh agama yang bernaung di bawah Kementerian Agama dewasa ini dipandang sangat penting dalam masyarakat Indonesia. Mereka dipandang berkontribusi dalam memelihara keharmonisan dalam masyarakat dan juga mendukung kampanye moderasi beragama. Sebelumnya, penyuluh agama hanya melayani nasihat maupun bantuan keagamaan kepada masyarakat dengan profesi khusus seperti polisi, tentara, dan juga mereka yang tinggal di asrama-asrama. Belakangan baru mereka melayani masyarakat secara luas. Namun sayangnya, perhatian kepada mereka terutama kebutuhan dan akses akan bahan bacaan keagamaan mereka masih tergolong rendah. Artikel ini, yang dihasilkan dari penelitian lapangan di Sulawesi Utara dan menggunakan mixed method ini, menggambarkan bagaimana para penyuluh agama itu memperoleh sumber bacaannya. Salah satu temuan pentingnya adalah para penyuluh agama mampu secara swadaya menutupi kebutuhan buku teks dan literatur keagamannya dengan cara swadayaKata Kunci: Literasi, Literatur Keagamaan, Penyuluh Agama Islam (dai), Revolusi Ekspresif.